Design, Synthesis, and Development of pyrazolo[1,5-a]pyrimidine Derivatives as a Novel Series of Selective PI3Kδ Inhibitors: Part I-Indole Derivatives - Mariola Stypik; Marcin Zagozda; Stanisław Michałek; Barbara Dymek; Daria Zdżalik-Bielecka; Maciej Dziachan; Nina Orłowska; Paweł Gunerka; Paweł Turowski; Joanna Hucz-Kalitowska; Aleksandra Stańczak; Paulina Stańczak; et al. (MDPI AG, 2022)
Phosphoinositide 3-kinase δ (PI3Kδ), a member of the class I PI3K family, is an essential signaling biomolecule that regulates the differentiation, proliferation, migration, and survival of immune cells. The overactivity of this protein causes cellular dysfunctions in many human disorders, for example, inflammatory and autoimmune diseases, including asthma or chronic obstructive pulmonary disease (COPD). In this work, we designed and synthesized a new library of small-molecule inhibitors based on indol-4-yl-pyrazolo[1,5-a]pyrimidine with IC50 values in the low nanomolar range and high selectivity against the PI3Kδ isoform. CPL302253 (54), the most potent compound of all the structures obtained, with IC50 = 2.8 nM, is a potential future candidate for clinical development as an inhaled drug to prevent asthma.